(untitled) (University Journal of Zoology, Rajshahi University, 2012)
The seasonal abundance of spider mite T. urticae on twenty vegetable and twenty four ornamental plants in Rajshahi was conducted during August 2010 to January 2011. The mite was present on joscpks coat, kathua, ladys finger, cucumber, brinjal, tomato, bottle gourd, bean, loofah, spinach, bitter melon, pointed gourd, radish, and cowpea but no mite was recorded on other six plants. But all the ornamental plants bagan-bilash, bottlebrush, nayantara, morog-jhuti, hasnahena, chandramallika, dalia, krisno-chura, togor, joba, madhobilata, rongon, beli, daisy, sondhamaloti, kamini, musanda, rakto-karobi, shewli, kath-golap, rajanigandha, golap, ganda, zinia contained mites. The pick population was prevailed during August. The increase of mite number is directly related with the increase of temperature. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10745 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 37-40